2013
DOI: 10.1111/ajco.12095
|View full text |Cite
|
Sign up to set email alerts
|

The significance of subcarinal dissection in esophageal cancer surgery

Abstract: Subcarinal dissection is still necessary in esophagectomy for esophageal squamous cell carcinoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 17 publications
1
9
0
Order By: Relevance
“…Increasing evidences suggest that AEJ is different from gastric and esophageal adenocarcinoma in molecular features, pathological evolution, and clinical behavior [ 4 ]. The prognosis of AEJ patients remains still poor (five-year survival rate, 10%-15%), which is poorer than those with other gastric cancers [ 5 ], because most of these patients are diagnosed at an advanced stage. The diagnosis and prognosis promise of many molecular targeted agents that have been characterized in other tumors are still unclear in AEJ [ 6 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Increasing evidences suggest that AEJ is different from gastric and esophageal adenocarcinoma in molecular features, pathological evolution, and clinical behavior [ 4 ]. The prognosis of AEJ patients remains still poor (five-year survival rate, 10%-15%), which is poorer than those with other gastric cancers [ 5 ], because most of these patients are diagnosed at an advanced stage. The diagnosis and prognosis promise of many molecular targeted agents that have been characterized in other tumors are still unclear in AEJ [ 6 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies reported subcarinal node metastasis indicated worse prognosis10, 11, 28, 29. Given that subcarinal node metastasis was more likely associated with an advanced disease status, the value of subcarinal node dissection in thoracic ESCC was also investigated.…”
Section: Discussionmentioning
confidence: 99%
“…Subcarinal lymph node dissection is the standard operative strategy for thoracic esophageal cancer [13]. Though rare, right superior pulmonary vein (RSPV) anomaly runs behind the right main or intermediate bronchus [46].…”
Section: Introductionmentioning
confidence: 99%